Perceived Conventionality in Co-speech Gestures Involves the Fronto-Temporal Language Network - Wolf, Dhana; Rekittke, Linn-Marlen; Mittelberg, Irene; Klasen, Martin; Mathiak, Klaus (Frontiers in Human Neuroscience, 2017)
Face-to-face communication is multimodal; it encompasses spoken words, facial expressions, eye gaze and co-speech gestures. While linguistic symbols (e.g., spoken words or signs in sign language) are highly conventional communicative signs with defined meanings, gesture vary in their degree of conventionality. Bodily signs may have a general accepted or conventionalized meaning (e.g., a head shake) or less so (e.g., self-grooming). The classical language networks can be expected to contribute to the subjective perception of conventionality in co-speech gestures, i.e., left hemispheric inferior frontal gyrus (IFG, Broca’s area) and the posterior superior temporal gyrus (pSTG, Wernicke’s area). This hypothesis was tested in 36 subjects watching video-recorded story retellings during a behavioral and an fMRI experiment. During each video clip, the subjects attended either to perceived conventionality or to a control task (any hand movements or gesture-speech relations). Covariance analyses assessed task effects on behavioral responses and functional data. The conventionality task significantly increased covariance of the button press time series and neuronal synchronization in the left IFG over the comparison with other tasks. In the IFG, synchronous activity was observed during the conventionality task only. In contrast, the left pSTG exhibited correlated activation patterns during all conditions with an increase in the conventionality task at the trend level only. Conceivably, the left IFG can be considered a core region for the processing of perceived conventionality in co-speech gestures similar to spoken language. In general, the interpretation of conventional signs may rely on neural mechanisms that also engage in language comprehension.